Eksistensi Partai Politik Islam Menurut Persfektif Aktivis Organisasi Mahasiswa Islam Di Universitas Baturaja - Alip Susilowati Utama; Herwin Sagita Bela; Ikang Putra Anggara (Jurnal Pemerintahan dan Politik, 2021)
This research based on the background that political parties in general and Islamic parties in particular are experiencing serious problems, namely the contradiction between the role and function idealism of the realities of everyday political party life witnessed by the public. Political parties receive a negative stigma, for example parties are considered corrupt, feudal and do not think about the fate of the little people. Islamic parties, which have been the object of research studies in several general election competitions (elections), have not been able to win or win the majority of votes despite having cultural and even ideological closeness to Muslims in Indonesia. The method used in this research is qualitative with a descriptive analytical approach. The results show that Islamic parties are still in doubt about their commitment to carrying out their responsibilities and in general they have not attracted or been trusted by some activists of Islamic student organizations, others still provide opportunities and trust in the hope that Islamic parties can improve the negative image attached to their institutions. Keywords: political parties; student organizations; and Islam.